“A STUDY ON FINANCIAL ANALYSIS OF SELECTED AUTOMOBILE COMPANIES” - Pankajkumar Raval, Kirtan (International Journal of Psychosocial Rehabilitation, 2020)
Since ancient time, there is significant role of automobile industries in the economy of India. Modernization and globalization has given vast scope to the automobile industries in market capture and sales maximization. In India also there are several automobile manufacturers which are dealing in the varying product line related to automobile sector as per the trends and demand of the Indian market as well as requirements for establishing international benchmarks in terms of features. In this researcher paper researcher has tried to determine financial performance of the selected automobile companies because financial health of the automobile sector also places considerable role in the economy. Researcher has made an attempt to determine profitability and liquidity position of two automobile companies in this paper.